The Relationship Between Inclination To Change, Self-Efficacy And Resilience Among Drug Addicts In Kajang Prison - Norulhuda Bin Mat Rozei (Universiti Sains Islam Malaysia, 2024)
Matric: 3211013 (FKP)-Restricted until July 2025